Intensive Care Pressure Injuries: A Cohort Study Using the CALCULATE and Braden Scales - Vocci, Marcelli Cristine; Lopes Saranholi, Taís; Amante Miot, Hélio; Fernandes Abbade, Luciana Patricia (Wolters Kluwer, 2022)
OBJECTIVE: Identify both the risk of developing pressure injuries (PIs) by applying the CALCULATE (CriticAL Care pressure ULcer Assessment Tool made Easy) and Braden Scales and the incidence of PIs in adult patients in intensive care. METHODS: This prospective cohort study was conducted from March 2016 to February 2017 in an adult ICU. The Braden and CALCULATE scales were applied every 48 hours until medical discharge, death, or PI development. RESULTS: The sample included 100 patients. The investigators obtained 818 evaluations (409 Braden and 409 CALCULATE) with an average of 4.1 observations per patient. According to the CALCULATE scale, 49 participants (49%) were classified as very high risk, compared with 40 participants (40%; P = .204) according to the Braden Scale. Thirty-five patients developed 37 PIs, with a total incidence of 35%. The mean age of patients who developed PIs was 60.3 (SD, 13.7) years, and they averaged 9.2 (SD, 6.8) days of hospitalization, with diagnoses related to cardiorespiratory and neurologic diseases and associated comorbidities of hypertension, diabetes mellitus, and smoking. The most affected site was the sacral region; 64.9% of the injuries were classified as stage 1. CONCLUSIONS: Patients in intensive care were high risk according to both PI scales, and many developed PIs. It is evident that even when preventive measures are used, they are insufficient without the implementation of preventive protocols.